Immune Alterations in a Patient With Hyperornithinemia-Hyperammonemia-Homocitrullinuria Syndrome: A Case Report - Silvera-Ruiz, Silene M.; Gemperle, Corinne; Peano, Natalia; Olivero, Valentina; Becerra, Adriana; Häberle, Johannes; Gruppi, Adriana; Larovere, Laura E.; Motrich, Ruben D. (Frontiers in Immunology, 2022)
The hyperornithinemia-hyperammonemia-homocitrullinuria (HHH) syndrome is a rare autosomal recessive inborn error of the urea cycle caused by mutations in the SLC25A15 gene. Besides the well-known metabolic complications, patients often present intercurrent infections associated with acute hyperammonemia and metabolic decompensation. However, it is currently unknown whether intercurrent infections are associated with immunological alterations besides the known metabolic imbalances. Herein, we describe the case of a 3-years-old girl affected by the HHH syndrome caused by two novel SLC25A15 gene mutations associated with immune phenotypic and functional alterations. She was admitted to the hospital with an episode of recurrent otitis, somnolence, confusion, and lethargy. Laboratory tests revealed severe hyperammonemia, elevated serum levels of liver transaminases, hemostasis alterations, hyperglutaminemia and strikingly increased orotic aciduria. Noteworthy, serum protein electrophoresis showed a reduction in the gamma globulin fraction. Direct sequencing of the SLC25A15 gene revealed two heterozygous non-conservative substitutions in the exon 5: c.649G>A (p.Gly217Arg) and c.706A>G (p.Arg236Gly). In silico analysis indicated that both mutations significantly impair protein structure and function and are consistent with the patient clinical status confirming the diagnosis of HHH syndrome. In addition, the immune analysis revealed reduced levels of serum IgG and striking phenotypic and functional alterations in the T and B cell immune compartments. Our study has identified two non-previously described mutations in the SLC25A15 gene underlying the HHH syndrome. Moreover, we are reporting for the first time functional and phenotypic immunologic alterations in this rare inborn error of metabolism that would render the patient immunocompromised and might be related to the high frequency of intercurrent infections observed in patients bearing urea cycle disorders. Our results point out the importance of a comprehensive analysis to gain further insights into the underlying pathophysiology of the disease that would allow better patient care and quality of life.